PENGARUH PLATFORM MEDIA SOSIAL TERHADAP MINAT GENERASI MILENIAL DALAM BERINVESTASI DI PASAR MODAL - Findri Firdhausa; Rani Apriani (SUPREMASI HUKUM, 2021)
Technology is a symbol of technological development progress. Millennials are considered technologically literate who currently provide facilities for investors to freely choose how to invest. Information about the types and ways of investment is available so abundant, especially with the internet media, potential investors can search for as much information as possible. Library Research studies libraries and other scientific works related to the problems studied, Normative legal research in the form of data obtained from literature studies. Nowadays millennials are starting to be interested in investing in the stock exchange. According to Indonesia Stock Exchange data about 60-70% of young investors aged up to 40 years invest in the stock exchange. The increase in millennial retail investors is also happening because the ordering system can be done online making transactions easier. Investment interest in Indonesia has continued to grow in recent times. Keywords: Technology, Millennials, Investments.